Multi-product bargaining, bundling, and buyer power - Markus Dertwinkel-Kalt; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
We re-consider the bilateral bargaining problem of a multi-product, manufacturer-retailer trading relationship. O'Brien and Shaffer (Rand JE 35:573-598, 2005) have shown that the unbundling of contracts leads to downward distorted production levels if seller power is strong, while otherwise the joint profit maximizing quantities are contracted (which is also always the case when bundling contracts are feasible). We show that the unbundling of contracts also leads to downward distorted output levels when the buyer firm has sufficient (Nash) bargaining power (i.e., buyer power). Our result is driven by cost substitutability (diseconomies of scope).
Keywords: L13; L41; K21; 330; Vertical Restraints; Bundling; Buyer Power